Functional Chitosan and Its Derivative-Related Drug Delivery Systems for Nano-Therapy: Recent Advances - Zixu Wang; Fangying Yu; Fuqiang Hu (MDPI AG, 2024)
In the struggle against diseases, the development of nano-therapy has certainly been a tremendous progression owing to the various superiority, and chitosan is no doubt a kind of prominent biopolymer material with versatility for applications in disease treatments. For the rational construction of chitosan-related nano-biodevices, it is necessary to pay full attention to the material itself, where it is the material properties that guide the design criteria. Additionally, the well-matched preparation methods between material carriers and therapeutic agents draw much attention to the final construction since they seem to be more realistic. In detail, we present a comprehensive overview of recent advances in rational construction of chitosan-related nano-therapies with respect to material-property-oriented design criteria and preparation methods in the current review article, based on the foundation of continuous investigations. Based on this review, a portion of the various uses of chitosan-related nano-biodevices for biomedical applications are specifically discussed. Here, the strategies demonstrate the versatility of chitosan well, and the concept of being simple yet effective is well illustrated and vividly communicated. Altogether, a fresh concept concerning multi-functional chitosan and its derivative-related drug delivery systems for nano-therapy is proposed in this review, and this could be applied to other materials, which seems to be a novel angle.